(3cTa GdZeI aj CYJbGO Cgd GdSfIs
(3ChdgG (B:s
(3GdMeO ddg hcai CeG HYO agPG cJGH cTa GdZeI ai CYJbGO Cgd GdSfI GNJUQJ ajg cJGH GdYGde GdQHGfi GHh GdbGSe GddGdcGFi GdWHQi hde CMPa efg Shi GdGSGfjO s
(3BNQgG (B:s
(3hSGdJ GdfUGQi ef NjQ Cgd edJce abGdhG MhGQi YjSi hSCdJ GdQGaVI ef TQ Cgd edJce abGdhG MhGQi eMeO JeJ gPg GdfSNI efg GdKbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds